Physicochemical and Pharmacokinetic Analysis of Anacardic Acid Derivatives - Zafar, Fahmina (ACS Omega, 2020)
[Image: see text] Anacardic acid (AA) and its derivatives are well-known for their therapeutic applications ranging from antitumor, antibacterial, antioxidant, anticancer, and so forth. However, their poor pharmacokinetic and safety properties create significant hurdles in the formulation of the final drug molecule. As a part of our endeavor to enhance the potential and exploration of the anticancer activities, a detailed study on the properties of selected AA derivatives was performed in this work. A comprehensive analysis of the drug-like properties of 100 naturally occurring AA derivatives was performed, and the results were compared with certain marketed anticancer drugs. The work focused on the understanding of the interplay among eight physicochemical properties. The relationships between the physicochemical properties, absorption, distribution, metabolism, and excretion attributes, and the in silico toxicity profile for the set of AA derivatives were established. The ligand efficacy of the finally scrutinized 17 AA derivatives on the basis of pharmacokinetic properties and toxicity parameters was further subjected to dock against the potential anticancer target cyclin-dependent kinase 2 (PDB ID: 1W98). In the docked complex, the ligand molecules (AA derivatives) selectively bind with the target residues, and a high binding affinity of the ligand molecules was ensured by the full fitness score using the SwissDock Web server. The BOILED-Egg model shows that out of 17 scrutinized molecules, 3 molecules exhibit gastrointestinal absorption capability and 14 molecules exhibit permeability through the blood–brain barrier penetration. The analysis can also provide some useful insights to chemists to modify the existing natural scaffolds in designing new anacardic anticancer drugs. The increased probability of success may lead to the identification of drug-like candidates with favorable safety profiles after further clinical evaluation.